DETERMINATION OF SEVERAL IMPORTANT PARAMETERS OF HOLLOW ELECTRODES ABNORMAL GLOW DISCHARGE PLASMA UNDER THE INFLUENCE OF MAGNETIC FIELD AT DIFFERENT GAS PRESSURES - Karim, Pshtiwan M.; Sadiq, Diyar A.; Al-Hakary , Shamo K. (Science Journal of University of Zakho, 2023)
This paper investigates the impact of an axial magnetic field on several plasma parameters of hollow electrode argon abnormal glow discharge. The discharge is generated by applying a DC voltage ranging from 0-6KV. By varying the pressure and magnetic field strength (0-25mT), the plasma potential, frequency, and degree of ionization were measured. The plasma potential, frequency, and degree of ionization were evaluated using spectroscopic measurements of the electron temperature and density. The results of the experiment show that the plasma potential decreases as the magnetic field strength increases, while the plasma frequency increases for lower pressure but reaches a constant value for higher pressure due to the increasing number of excitation collisions among the plasma-charged particles. The degree of ionization, determined using the ideal gas law, shows a near-linear relationship with the axial magnetic field at both low and high pressure.